Characterization of γδ T Cells in Intestinal Mucosa From Patients With Early-Onset or Long-Standing Inflammatory Bowel Disease and Their Correlation With Clinical Status. (22nd January 2019) - Lo Presti, Elena; Di Mitri, Roberto; Mocciaro, Filippo; Di Stefano, Anna Barbara; Scibetta, Nunzia; Unti, Elettra; Cicero, Giuseppe; Pecoraro, Giulia; Conte, Elisabetta; Dieli, Francesco; Meraviglia, Serena
Abstract: Background and Aims: Inflammatory bowel disease [IBD] is a complex chronic inflammatory disease of the human gut with no clear aetiology. Traditionally, dysregulated adaptive immune responses play an important role even though accumulating evidence suggests a role also for innate immunity. Because of the well-known plasticity of γδ T cells, we investigated their percentage occurrence, phenotypic features and effector functions in the intestinal mucosa of early-onset and long-standing IBD patients, as compared to healthy subjects. Methods: Fresh biopsies from 30 Crohn's disease and ulcerative colitis patients were obtained and digested, and cells were analysed by flow cytometry. Results: We found a reduced frequency of Vδ1 T cells in tissue from early and late IBD patients (2.24% and 1.95%, respectively, vs 5.44% in healthy tissue) but an increased frequency of Vδ2 T cells in the gut of late IBD patients (3.19% in late patients vs 1.5% in early patients and 1.65% in healthy tissue). The infiltrating Vδ2 T cells had predominant effector memory and terminally differentiated phenotypes and produced elevated levels of tumour necrosis factor-α [TNF-α] and interleukin-17 [IL-17]. The frequency of tissue Vδ2 T cells correlated with the extent of the inflammatory response and the severity of IBD. Conclusion: Our study shows that tissue Vδ1 T cells are decreased in IBD patients while Vδ2 T cells are increased in the gut of IBD patients and contribute to TNF-α production. Moreover, we identify an as yet unappreciated role of Vδ2 T cells in IL-17 production in the gut of long-standing IBD patients, suggesting that they also participate in the chronic inflammatory process.